The Relationship Between Local Field Potentials and the Blood-Oxygenation-Level Dependent MRI Signal Can Be Non-linear - Zhang, Xiaodi; Pan, Wen-Ju; Keilholz, Shella (Frontiers in Neuroscience, 2019)
Functional magnetic resonance imaging (fMRI) is currently one of the most important neuroimaging methods in neuroscience. The image contrast in fMRI relies on the blood-oxygenation-level dependent (BOLD) signal, which indirectly reflects neural activity through neurovascular coupling. Because the mechanism that links the BOLD signal to neural activities involves multiple complicated processes, where neural activity, regional metabolism, hemodynamics and the BOLD signal are all inter-connected, Understanding the quantitative relationship between the BOLD signal and the underlying neural activities is crucial to interpreting fMRI data. Simultaneous local field potential (LFP) and fMRI recording provides a method to study neurovascular coupling. There were a few studies that have shown nonlinearities in stimulus related responses, but whether there is any nonlinearity in LFP – BOLD relationship at rest has not been specifically quantified. In this study, we analyzed the simultaneous LFP and resting state-fMRI data acquired from rodents, and found that the relationship between LFP and BOLD is nonlinear under isoflurane (ISO) anesthesia, but linear under dexmedetomidine (DMED) anesthesia. Subsequent analysis suggests that such nonlinearity solely comes from the non-Gaussian distribution of LFP power, and switching from LFP power to LFP amplitude can alleviate the problem to a degree. We also confirmed that, despite the nonlinearity in the mean LFP – BOLD curve, the Pearson correlation between the two signals is relatively unaffected.